Wastewater analysis reveals spatial pattern in consumption of anti-diabetes drug metformin in China. (May 2019) - Yan, Ji-Hao; Xiao, Yang; Tan, Dong-Qin; Shao, Xue-Ting; Wang, Zhuang; Wang, De-Gao
Abstract: Metformin has been widely used as an oral drug for the treatment of diabetes mellitus. However, its consumption can be influenced by many economic and social factors. In this study, we investigated the spatial consumption pattern of metformin in China through wastewater-based epidemiology (WBE) approach. Influent wastewater samples were collected from 21 wastewater treatment plants (WWTPs) in 19 cities of the northeast China. A method using solid-phase extraction combined with N-Methyl-bis (trifluoroacetamide) derivatization for GC-MS detection was applied for metformin analysis. In 21 days, metformin showed high stability in wastewater at 24 °C and −20 °C. The mean concentrations of metformin in all WWTPs ranged from 2.42 μg L −1 to 53.6 μg L −1 . The consumption of metformin was 0.66–15.6 mg d −1 capita −1 with the mean value of 5.54 ± 4.28 mg d −1 capita −1 . The prevalence of metformin ranged from 0.09% to 2.10% with an average of 0.74%. Both the consumption and prevalence of metformin displays significant spatial variations in northeast China. A statistical correlation analysis indicated that the consumption of metformin increases with the decrease of per capita disposable income of urban residents. To further predict the use of metformin in China, we developed a regress model and depicted a consumption map. The annual consumption of urban residents in Chinese provinces range from 1085-63, 828 kg yr −1 with mean value of 25, 347 kg yr −1, which would provide a certain reference value for public health care and diabetes control. Highlights: Metformin use in China was the first time evaluated by wastewater-based epidemiology. Significant spatial variation was shown in the northeast China. Consumption of metformin exhibited increase with the decreasing per capita income. A regress model was provided for the forecast of metformin consumption in China.